2007
DOI: 10.1111/j.1467-8683.2007.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Private vs State Ownership and Earnings Management: evidence from Chinese listed companies

Abstract: In this study, we investigate the role played by a firm's ownership structure in earnings management, with reference to the Chinese capital market. We measure the impacts of both ownership concentration and different ownership types, specifically the difference between the state as blockholder and private blockholders.Analysing 273 privately-owned and state-owned Chinese companies listed in 2002, we establish a link between ownership structure and firms' earnings management practices. Our results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
304
4
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(347 citation statements)
references
References 63 publications
32
304
4
7
Order By: Relevance
“…An important feature of Chinese firms is state ownership (Chen & Young, 2010;Morck et al, 2008). While the role of state ownership in the domestic operation and governance of Chinese firms has been extensively researched (Ding, Zhang, & Zhang, 2007;Young, Peng, Ahlstrom, Bruton, & Jiang, 2008;Zou & Adams, 2008), limited attention has been paid to the role of state ownership in the internationalization of Chinese firms (Chen & Young, 2010). Our study addresses this research gap by revealing the role of state ownership in Chinese firms' FDI ownership decisions.…”
Section: Introductionmentioning
confidence: 94%
“…An important feature of Chinese firms is state ownership (Chen & Young, 2010;Morck et al, 2008). While the role of state ownership in the domestic operation and governance of Chinese firms has been extensively researched (Ding, Zhang, & Zhang, 2007;Young, Peng, Ahlstrom, Bruton, & Jiang, 2008;Zou & Adams, 2008), limited attention has been paid to the role of state ownership in the internationalization of Chinese firms (Chen & Young, 2010). Our study addresses this research gap by revealing the role of state ownership in Chinese firms' FDI ownership decisions.…”
Section: Introductionmentioning
confidence: 94%
“…Further, the impact of state ownership on performance changes over time. For example, Carney et al (2009) With respect to expropriation, there is evidence that state ownership relates negatively to intercorporate loans (Jiang et al, 2010), earnings management (Cheng et al, 2010;Ding et al, 2007), and financial fraud (Yuan, Yuan, & Deng, 2008), suggesting that the state is less likely to engage in expropriation. However, there is evidence that state ownership relates positively to related-party resource transfers/transactions (Huyghebaert & Wang, 2012;Shan, 2013) and financial fraud (Firth, Rui, & Wu, 2011;Hou & Moore, 2010).…”
Section: Internal Mechanism: Ownership Structurementioning
confidence: 99%
“…In addition, the majority of previous studies have investigated Chinese listed companies (Aharony, Lee, & Wong, 2000;Chen & Yuan, 2004;Ding, Zhang, & Zhang, 2007;Liu & Lu, 2007;Wang & Yung, 2011). Ding et al (2007) and Wang and Yung (2011) have found that state-owned companies manage earnings less than privately-owned companies. Conversely, Aharony et al (2000), Chen and Yuan (2004) and Liu and Lu (2007) have found that state-owned companies manage earnings more than privately-owned ones do.…”
Section: State Ownership and Earnings Managementmentioning
confidence: 99%
“…As in previous studies (e.g. Demsetz & Lehn, 1985;Prowse, 1992;Claessens & Djankcov, 1999;Ding et al, 2007), it is defined as the proportion of shares held by the majority shareholder.…”
Section: Independent Variablesmentioning
confidence: 99%